Analysis of Harvest Area, Productivity, and Fertilizer Prices on Farmer Exchange Rate of Rice Food Crop Sub-Sector in Bengkulu Province - Septia Nur Cahyani; Hermanto, Bambang Agoes; Dien Ajeng Fauziah (Indonesian Journal of Economic & Management Sciences, 2024)
This study examines the relationship between harvest area, productivity, and fertilizer prices on the farmer exchange rate of the rice food crop sub-sector in Bengkulu Province. This research is an explanatory research study with secondary data consists of monthly data from 2018 to 2022, resulting in a total of 60 observations. A multiple linear regression analysis was conducted using the OLS analysis model with Eviews 9. The results of the study indicate that the harvest area has a negative and insignificant effect on the farmer's exchange rate. Furthermore, the productivity of rice yield has a negative and significant effect on the farmer's exchange rate. This suggests that the lower the agricultural productivity, the more significant the farmer exchange rate. With regard to fertilizer prices, the results indicate a positive and significant impact on the farmer exchange rate. This implies that an increase in fertilizer prices leads to a corresponding increase in the farmer exchange rate